A Case of Dextrocardia with Single Atrium with A-V canal Defect with Pulm Hypertension- Case Report with Review - Faruque, Md; Rashid, Md Abdur; Muttalib, MA; Islam, Syed Aminul; Rahman, Md Hafizur (University Heart Journal, 2013)
Congenital Heart disease is although uncommon but is not rare. Complex congenital Heart disease is more rare. The survivality is less. Most of the patient die in the Early childhood. Our patient survive up to the age of 23 yrs. Early diagnosis & early corrective surgery will prolong the survivality & even normal life. DOI: http://dx.doi.org/10.3329/uhj.v8i2.16086 University Heart Journal Vol. 8, No. 2, July 2012